Does physical activity reduce the risk of developing peptic ulcers?. Issue 2 (1st April 2000) - Cheng, Yiling; Macera, Caroline A; Davis, Dorothy R; Blair, Steven N
Abstract : Background —Although Helicobacter pylori has been identified as a major cause of chronic gastritis, not all infected patients develop ulcers, suggesting that other factors such as lifestyle may be critical to the development of ulcer disease. Aim —To investigate the role physical activity may play in the incidence of peptic ulcer disease. Methods —The subjects were men (8529) and women (2884) who attended the Cooper Clinic in Dallas between 1970 and 1990. The presence of gastric or duodenal ulcer disease diagnosed by a doctor was determined from a mail survey in 1990. Subjects were classified into three physical activity groups according to information provided at the baseline clinic visit (before 1990): active, those who walked or ran 10 miles or more a week; moderately active, those who walked or ran less than 10 miles a week or did another regular activity; the referent group consisting of those who reported no regular physical activity. Results —With the use of gender specific proportional hazards regression models that could be adjusted for age, smoking, alcohol use, body mass index, and self reported tension, active men were found to have a significant reduction in risk for duodenal ulcers (relative hazard (95% confidence interval) for the active group was 0.38 (0.15 to 0.94) and 0.54 (0.30 to 0.96) for the moderately active group). No association was found between physical activity and gastric ulcers for men or for either type of ulcer for women. Conclusions —Physical activity may provide a non-pharmacological method of reducing the incidence of duodenal ulcers among men.